Bio-optical and physiological patterns in Antarctic seaweeds: A functional trait based approach to characterize vertical zonation. (May 2019) - Gómez, Iván; Navarro, Nelso P.; Huovinen, Pirjo
Highlights: Photosynthesis and bio-optical traits define the zonation of Antarctic seaweeds. Thicker algae are well equipped to absorb the low irradiances at deeper locations. Delicate green algae with wide geographic distribution are mostly intertidal. Antarctic-Subantarctic thick leathery red algae dominate at upper subtidal zone. Endemic brown algae with thick morphology thrive at deeper subtidal zone. Antarctic algae show high short-term temperature and UV stress tolerance. Abstract: A suite of photosynthetic and bio-optical properties of 29 Antarctic seaweeds from Fildes Bay, King George Island, were studied in order to address the question whether their different functional traits, grouped according to gross morphology, bathymetric distribution, taxonomic category and biogeographic affinity, can explain the observed patterns of vertical distribution and relevant ecosystems services. Based on PCA analysis light requirements for photosynthesis (Ek ), thallus absorptance and thickness, photosynthetic efficiency (α) and tolerance to stress (UV and temperature) were the traits with the highest predictive value for vertical distribution of the studied Antarctic algae. In this context, the set of bio-optical traits were strongly related with a morphological adaptation to use the available light at different wavelengths at different depths: thick leathery and coarsely branched morphs, mostly red and brown algae, were well equipped to absorb the impoverished light field at deeper locations (lowest Ek values close to 36 μmol m −2  s −1 ), while sheet-like algae, especially green algae showed lower absorption at wavelengths that are rapidly attenuated with depth (highest Ek values of 260 μmol m −2  s −1 ). The studied algae showed high tolerance to stress measured in short-term exposures to UV radiation and enhanced temperature (7 °C). The stress tolerance was independent of gross morphology, while greatest differences were found along depth gradient and between algae of different biogeographic affinity. The studied traits were highly interlinked in terms of photosynthetic and bio-optical properties. Our trait based framework defined three major clusters of species: (1) delicate (filamentous and sheet-like) green algae, living mostly in the intertidal zone and with wide geographic distribution; (2) thick leathery Rhodophyta with Antarctic-Subantarctic origin, found mostly at shallow-subtidal locations; and (3) endemic Antarctic brown algae with thick morphology inhabiting the lower subtidal zone. Overall, these results highlight the importance of morpho-functional traits of macroalgae in explaining their distribution across a depth gradient and provide insights into their potential to endure a changing polar environment. This is relevant in Antarctic marine ecology as macroalgae underpin the biogeochemical processes at coastal ecosystems.